Frequency and management of non-obstetric fistula in the Democratic Republic of Congo: experience from Fistula Care Plus project - Delamou, Alexandre; Mpunga, Michel; Banze, Félicien; Nembunzu, Dolores; Raha, Kenny; Paluku, Justin; Kinja, Rachel; Kitambala, Esther; Aussak, Brian Tena-Tena; Bobina, Ruth Bulu; et al. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the frequency and management of non-obstetric fistula (NOF) in Democratic Republic of Congo (DRC). Methods: A retrospective cohort study reviewed patients’ medical records in three fistula repair sites supported by the USAID-funded Fistula Care Plus (FC+) Project, covering 1 January 2015 to 31 December 2017. Study variables included demographic characteristics, fistula etiology as reported by surgeon, fistula type (Waaldijk classification), and treatment outcomes. Results: Of 1984 women treated for female genital fistula between 2015 and 2017 in the three sites, 384 (19%) were considered to be NOF cases. 91% of these women resided in rural areas. 49.3% were married/in relationship at time of treatment compared to 69% before the fistula (p<0.001). Most (n=316; 82.3%) had no previous repair attempts and 96.2% had an intact urethra. Type III (n=247; 64.3%) and type I (n=121; 31.5%) fistulas (Waaldijk classification) were most common. The main causes of NOF were medical procedure (n=305; 79.4%), congenital origin (41; 10.7%) or sexual assault (28; 7.3%). Caesarean section (n=234; 76.7%) and hysterectomy (n=54; 17.7%) were the most common causative procedures. 369 women with NOF received surgical repair (96%), mainly through routine services (n=317; 85.9%). At discharge, 353 women were closed and dry (95.7%) and 11 were closed with residual incontinence (3.0%). Conclusions: NOF, particularly due to iatrogenic causes, was relatively common in DRC. Surgical repair at FC+-supported sites led to good clinical outcomes. However, to achieve a fistula-free generation in DRC, prevention of iatrogenic fistula is needed, requiring improved quality of maternal care.